Knowledge, attitudes and behavior of adolescents about reproductive health at Belgrade territory - Kisić-Tepavčević Darija; Šterić Milena; Kisić Vesna; Popović Aleksandra; Pekmezović Tatjana (Srpski Arhiv za Celokupno Lekarstvo, 2010)
Introduction. Over the past few years, the results of numerous studies have emphasized the importance of adolescents' insufficient knowledge about reproductive health (RH), which implies an increasing trend of unwanted pregnancies and sexually transmitted diseases (STDs). Objective. The aim of this study was to investigate knowledge, attitudes and behaviour of adolescents about RH in the population of Belgrade. Method. The study comprised 292 students from three secondary schools in Belgrade involved in the research February 1-15, 2008. The semistructured questionnaire about adolescents' knowledge, attitudes and behaviour about RH was filled in by themselves in presence of a student-investigator who provided assistance when necessary. Statistical analysis included χ2 test and correlation analysis. Results. Most adolescents (70.5%) showed the medium level of knowledge about RH. In our study, 33.6% of adolescents were sexually active. Sexually active students achieved a better score on the test about RH compared with the students who have not had sexual intercourse yet (χ2-test=34.003; p<0.01). The average age of the first sexual intercourse was 16.5 years for females, and 15.7 years for males. The students with a lower average grade in school education experienced the first sexual intercourse earlier compared to the adolescents with a higher average grade during the school education (ρ=0.485; p<0.01). The most common (73.4%) source of information about RH is mass media. Conclusion. The results of our study indicate the need for more intensive and comprenhensive educational programmes in the area of RH for adolescents in our country.